Strategi Kepala Sekolah Dalam Meningkatkan Mutu Tenaga Pendidik pada SMP Swasta Dharma Bakti Besitang Tahun Pembelajaran 2024-2025 - Delpia, Rini; Sanjani, Maulana Akbar; Ismail, Ismail (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the strategies implemented by the principal in improving the quality of teaching staff at Dharma Bakti Besitang Private Junior High School, Langkat Regency, North Sumatra Province, during the 2024–2025 academic year. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation involving the principal, teachers, and administrative staff. The findings reveal that the principal employs several key strategies, including skill improvement through seminars, training, and additional teaching hours; motivational support; regular supervision; resource management; role modeling; and reward provision. These strategies have contributed to increased teacher pedagogical competence, improved discipline, higher work motivation, and better teaching performance. The study also shows that consistent supervision and structured professional development activities play a significant role in strengthening teacher commitment and instructional quality. Practically, this research highlights the importance of strategic leadership in enhancing teacher quality, offering insights for school leaders seeking to implement effective teacher development programs. The study contributes to the understanding of principal leadership practices in private junior high schools, particularly within the context of rural educational settings in Indonesia.